Tudo ou tudo: a concretude e o luminoso na poética de Arnaldo Antunes - Oliveira, Daniele Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In t his thesis we discusst he work of Arnaldo Antunes critically creatively. Author 's works were studied in various art forms practiced by him as calligraphy, perfor mance, music, and writing. Here is the wor k of Arnaldo Antunes, in a context that opens the Transemiose

Nesta Tese abordamos o trabalho de Arnaldo Antunes de f orma crítico-criativa. Foram estudados trabalhos do autor nas diversas linguagens artísticas praticadas por ele, como a caligrafia, a performance, a música, e a escrita. Apresentamos a obra de Arnaldo Antunes, em um context o em que se abre a Transemiose
Keywords: Antunes, Arnaldo 1960; Poesia visual; Arte moderna - Séc. XXI; Performance (Arte); Caligrafia; Poesia concreta; Visual poetry